Anthraquinone metabolites isolated from the rhizosphere soil Streptomyces of Panax notoginseng (Burk.) F. H. Chen target MMP2 to inhibit cancer cell migration. (10th August 2023) - Xue, Jin-Yan; Wu, Ying-Ying; Han, Yu-Ling; Song, Xin-Yu; Zhang, Meng-Yue; Cheng, Juan; Lin, Bin; Xia, Ming-Yu; Zhang, Yi-Xuan
Abstract: Ethnopharmacological relevance: Panax notoginseng (Burk.) F. H. Chen belongs to the Araliaceae family. It has been used by traditional Chinese people in Northeast Asia for centuries as an antidiabetic, antioxidant, antitumor agent, etc . Endophytic or rhizospheric microorganisms play key roles in plant defense mechanisms, and they are essential in the discovery of pharmaceuticals and valuable new secondary metabolites. In particular, endophytic or rhizospheric microorganisms of traditional medicinal plants. Aim of the study: To discover valuable new secondary metabolites from rhizosphere soil Streptomyces sp. SYP-A7185 of P. notoginseng, and to explore potential bioactivities and targets of metabolites protrusive function. Materials and methods: The metabolites were obtained via column chromatography and identified by multiple spectroscopic analyses. The antitumor, antioxidant, antibacterial, and antiglycosidases effects of isolated metabolites were tested using 3-[4, 5-dimethythiazol-2-yl]-2, 5-diphenyltetazolium bromide (MTT), 2, 2-diphenyl-1-picrylhydrazyl (DPPH), 96-well turbidimetric, and α -glucosidase inhibitory assays. The potential antitumor targets were predicted through network pharmacological approaches. The interactions between metabolites and target were verified by molecular docking and biolayer interferometry (BLI) assay. The effects of cancer cells migration were detected through wound healing assays in A549 and MCF-7. Other cellular validation experiments including reverse transcription-quantitative PCR (RT‒qPCR) and western blotting (WB) were used to confirm the hypothesis of network pharmacology. Results: Five different chemotypes of anthraquinone derivatives (1 –10 ), including six new compounds (3, 6 –10 ), were identified from Streptomyces sp. SYP-A7185. Compounds 1 –6 and 9 displayed moderate to strong cytotoxicity on five human cancer cell lines (A549, HepG2, MCF-7, MDA-MD-231, and MGC-803). Moreover, matrix metalloproteinase-2 (MMP2) were predicted as a potential antitumor target of metabolites 1 –6 and 9 by comprehensive network pharmacology analysis. Later, BLI assays revealed strong intermolecular interactions between MMP2 and antitumor metabolites, and molecular docking results showed the interaction of metabolites 1 –6 and 9 with MMP2 was dependent on the crucial amino acid residues of LEU-83, ALA-84, LEU-117, HIS-131, PRO-135, GLY-136, ALA-140, PRO-141, TYR-143, and THR-144. These results implied that metabolites (1 –6 and 9 ) might inhibit cancer cell migration besides cancer cell proliferation. After that, the cell wound healing assay showed that the cell migration processes were also inhibited after the treatments of compounds 1 and 3 in A549 and MCF-7 cells. In addition, the RT‒qPCR and WB results demonstrated that the gene expression levels of MMP2 were decreased after the treatment with compounds 1 and 3 in A549 and MCF-7 cells. Besides, compound 2 displayed moderate antioxidant activity (EC50, 27.43 μM), compounds 3 and 6 exhibited moderate antibacterial activity, and compound 3 inhibited α -glucosidase with an IC50 value of 13.10 μM. Conclusions: Anthraquinone metabolites, from rhizosphere soil Streptomyces sp. of P . notoginseng, possess antitumor, antioxidant, antibacterial, and antiglycosidase activities. Moreover, metabolites 1 and 3 inhibit cancer cells migration through downregulating MMP2. Graphical abstract: Image 1 Highlights: Anthraquinone metabolites from rhizosphere soil Streptomyces of Chinese herbs Panax notoginseng (Burk.) F. H. Chen were studied. Ten anthraquinone derivatives were isolated including six new compounds. Anthraquinones (1 –10 ) from Streptomyces sp. SYP-A7185 exerted various bioactivities. Anthraquinone metabolites 1 and 3 inhibit cancer cells migration through downregulating MMP2.